2010
DOI: 10.1002/cssc.201000027
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance, Superparamagnetic, Nanoparticle‐Based Heavy Metal Sorbents for Removal of Contaminants from Natural Waters

Abstract: We describe the synthesis and characterization of high-performance, superparamagnetic, iron oxide nanoparticle-based, heavy metal sorbents, which demonstrate excellent affinity for the separation of heavy metals in contaminated water systems (i.e., spiked Columbia River water). The magnetic nanoparticle sorbents were prepared from an easy-to-synthesize iron oxide precursor, followed by a simple, one-step ligand exchange reaction to introduce an affinity ligand to the nanoparticle surface that is specific to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 48 publications
1
80
0
1
Order By: Relevance
“…Many reports discussed the influence of different parameters on the removal of metal ions by Fe 3 O 4 magnetic nanoparticles [47,123]. For example, the adsorption efficiency of Ni(II), Cu(II), Cd(II) and Cr(VI) ions by Fe 3 O 4 nanoparticles was strongly dependent on pH, temperature, amount of the adsorbent and the incubation time [124][125][126][127]. Further, a higher removal efficiency of these metal ions at a 3.5 mg mL [124][125][126][127].…”
Section: Metal Oxide-based Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports discussed the influence of different parameters on the removal of metal ions by Fe 3 O 4 magnetic nanoparticles [47,123]. For example, the adsorption efficiency of Ni(II), Cu(II), Cd(II) and Cr(VI) ions by Fe 3 O 4 nanoparticles was strongly dependent on pH, temperature, amount of the adsorbent and the incubation time [124][125][126][127]. Further, a higher removal efficiency of these metal ions at a 3.5 mg mL [124][125][126][127].…”
Section: Metal Oxide-based Nanomaterialsmentioning
confidence: 99%
“…For example, the adsorption efficiency of Ni(II), Cu(II), Cd(II) and Cr(VI) ions by Fe 3 O 4 nanoparticles was strongly dependent on pH, temperature, amount of the adsorbent and the incubation time [124][125][126][127]. Further, a higher removal efficiency of these metal ions at a 3.5 mg mL [124][125][126][127]. Singh et al [46] reported the removal of toxic metal ions from wastewater using carboxyl-, amine-and thiol-functionalized Fe 3 O 4 nanoparticles (succinic acid, ethylenediamine and 2,3-dimercaptosuccinic acid, respectively).…”
Section: Metal Oxide-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimercaptosuccinic acid (DMSA) is one surface coating that has been studied because of its stable molecular structure across a wide pH range and ability to prevent particle aggregation at high ionic strengths [21]. Secondary molecules can also be bound to the carboxylates on the DMSA molecule once adsorbed to the γ-Fe 2 O 3 nanoparticles.Coating Fe 3 O 4 nanoparticles with DMSA increased copper adsorption in synthetic groundwater and river water from 3.45 mgCu(II)/g to 36.49 mgCu(II)/g and 23.82 mgCu(II)/g, respectively [19,20]. Warner et al found that DMSA-coated γ-Fe 2 O 3 nanoparticles having a diameter of 7.2 nm adsorbed 23.8 mg Cu(II)/g compared to 3.5 mg Cu(II)/g for bare γ-Fe 2 O 3 nanoparticles of equal diameter [19].…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic is particularly attractive as it affords the possibility of separating the adsorbent/adsorbate complex from solution without the need for clarification or filtration processes [16]. For these reasons they have become the focus of a large body of research on using magnetic nanoparticle for metal recovery from solution [14,[17][18][19][20]. γ-Fe 2 O 3 nanoparticles can adsorb metals in both a bare or surface modified state.…”
Section: Introductionmentioning
confidence: 99%